Pemberdayaan Pengepul Sampah Dengan KSM Gebres Cemerlang Melalui Pengolahan Plastik Menjadi Paving Block - Setyo Rini, Asih; Ahmad Rizky Pratama; Imas Nurul Meilinda; Suci Safitri; Yosua Rosevelt Ayawaila (LPPM ITEBA, 2026)
Plastic waste, which is difficult to decompose naturally, has become a serious environmental problem due to its potential to pollute soil, water, and air. This activity aims to process plastic waste from waste-collecting MSMEs into functional paving blocks with economic value. The program was carried out with partners from a Waste-Collecting MSME in Serang and KSM Gebers Cemerlang MSME in Cilegon using the 5W+1H method through observation, interviews, documentation, and direct practice of paving block production. The process included sorting, washing, cutting, melting, molding, and cooling of plastic waste. The results show that plastic waste can be successfully processed into paving blocks with good shape and potential market value, and the cleaning and cutting stages improved melting efficiency, while water cooling helped maintain the product form. It can be concluded that processing plastic waste into paving blocks is an applicable solution to reduce plastic waste generation and support the circular economy, although further testing is required to ensure product strength and quality according to standards.